2017
DOI: 10.1016/j.ijsu.2017.05.045
|View full text |Cite
|
Sign up to set email alerts
|

The Established Acute Surgical Unit: A reduction in nighttime appendicectomy without increased morbidity

Abstract: IIb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 35 publications
4
23
0
Order By: Relevance
“…This is consistent with data from a recent meta‐analysis which showed that delaying surgery for presumed uncomplicated appendicitis for up to 24 hours after admission did not result in more complications . Our results also showed that the proportion of operations performed overnight was significantly lower in the contemporary cohort without any obvious adverse consequences, reinforcing the findings of Allaway et al . in their 5‐year follow‐up study of appendicectomy outcomes following the implementation of an ACS model at Nepean Hospital.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This is consistent with data from a recent meta‐analysis which showed that delaying surgery for presumed uncomplicated appendicitis for up to 24 hours after admission did not result in more complications . Our results also showed that the proportion of operations performed overnight was significantly lower in the contemporary cohort without any obvious adverse consequences, reinforcing the findings of Allaway et al . in their 5‐year follow‐up study of appendicectomy outcomes following the implementation of an ACS model at Nepean Hospital.…”
Section: Discussionsupporting
confidence: 89%
“…There have not been other substantive changes to the local health service over this time. This contrasts with other ACS units who have experienced substantially increased workload and commensurate expansion of resources such as the number of emergency theatres . One weakness of this study is that several potentially important confounders, such as patient comorbidities and socioeconomic status and the level of experience of the primary proceduralist, were not measured.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations